Assessing Clinicopathologic factors in uterine leiomyoma patients in East Libya. - A.R. Ashour, Guheina; S Elkwafi, Raja; Abd-alsalam Faitori Ali, Aya; Fadl-allah Al-Barghathi, Shahad; Abokhazim Al-sahati, Amani (Benghazi University Medical Journal, 2025)
Introduction: Uterine leiomyomas (ULs) are benign tumors of smooth muscle tissue; occur in women of reproductive age, with clinical manifestations depending on their size, and location. Aim: To assess the clinicopathologic factors related to uterine leiomyomas. Materials and methods: The data were collected from the Electronic Archive Unit, Benghazi Medical Center using structured forms. Descriptive, retrospective study was accomplished, using data over the period of Jan 2020-Dec 2021. Statistical analysis was done using IBM SPSS, version 20. Results: Seventy-three cases were included in the study with mean age of 43.31 ±7.31 years, (54.9%) of cases were in the age group 41-50 years, with statistically significant difference in the cases above forties. Blood group O+ represented in (32.9%) of total cases, followed by blood group A+. Uterine leiomyomas were higher among the married women (42.5%). Among the clinical features, menorrhagia was the common complaint in (50.7%) of cases. With statistically significant difference, Menorrhagia, Irregular bleeding, and Pain (pelvic / abdominal) were occurred more in the age group 41-50 years, while Dysmenorrhea and Infertility were in younger age between 31-40 years. Myomectomy was performed in (74%) of cases. Multiple uterine leiomyomas were in (54.8%) of cases. The mean tumor size was 6.75±4.25 cm. Associated changes are seen, the Endometrial hyperplasia was in one case, adenomyosis was found in 4 cases, chocolate cyst in 5 cases and simple cyst in one case. Conclusion: Uterine leiomyomas occur in childbearing age and premenopausal women, more in whom with blood group O+. The multiple leiomyomas were commoner than single. Married patients were more affected than the single. Menorrhagia was a frequent presenting complaint.